Influence of supplementation of black pepper powder through feed in broiler chickens on their growth performance, blood profile, meat sensory qualities and duodenum morphology - SINGH, JASWINDER; SHARMA, MANJINDER; MEHTA, NITIN; SINGH, N D; KAUR, PAVITER; SETHI, A P S; SIKKA, S S (The Indian Journal of Animal Sciences, 2018)
A study was conducted to evaluate the black pepper powder (BP) as phytogenic alternative to antibiotic growth promoters in broilers. One-day old broiler chicks (225) were randomly distributed to five treatments with three replicates of each. The dietary treatments comprised basal diet as control (C), antibiotic group receiving 0.1 g/kg of oxytetracycline (AB), 0.5, 1.0, and 1.5% of BP added to basal diet to formulate BPL (low), BPM (medium) and BPH (high) groups. Body weight and feed consumed were recorded weekly and accordingly feed conversion ratio and protein efficiency ratio were calculated. At the end of 5th week, 2 birds per replicate were sacrificed to determine the carcass characteristics, meat sensory evaluation, blood parameters, duodenum morphology and faecal microbial load. The result revealed that inclusion of black pepper powder at 0.5% level improved the weight gain, feed conversion ratio and protein efficiency ratio as compared to other treatments. The dietary regimes failed to affect the carcass parameters studied except the heart weight. Black pepper powder supplementation at all the three level studied improved the appearance, colour and overall acceptability score of meat as compared to control. Blood parameters data revealed improvement in haemoglobin and reduction in triglycerides and cholesterol level in BP supplemented groups as compared to control. BP supplementation affected the fat digestibility and calcium retention. It can be concluded that black pepper has the potential to replace the prevalent antibiotic growth promoters used in broiler chickens.